O vocabulário emocional de estudantes do ensino fundamental - Corrêa, Bruna Lima (2025)
The acquisition of a broad and accurate emotional vocabulary is essential for recognizing, interpreting, and managing emotions, as well as improving communication and strengthening interpersonal connections. As a right of basic education students, it is expected that, upon entering elementary school, they will already be able to express their emotions and feelings. With the aim of investigating the emotional vocabulary of elementary school students, this study constructed and validated an emotional task, which was applied to a sample of 231 students, of both sexes, from the 6th to 9th grades of a school in Sergipe, with ages ranging from 10 to 17 years old. The results indicated that the students presented an accurate emotional vocabulary for basic emotions, but limited for complex emotions, with the exception of “boredom”, “loneliness”, “anxiety” and “envy”, which, together with the basic emotions, made up the emotional vocabulary of the sample. The school year, age and sex of the participants did not exert a significant influence on performance in the task. The findings contribute to the understanding of the emotional vocabulary of Brazilian elementary school students, but highlight the need for further research to expand this understanding, especially on the influences of age and gender on the development of emotional vocabulary. Furthermore, this research paves the way for the use of artificial intelligence technologies as a viable and accessible alternative for proposing emotional tasks and research on emotions.